The Effect of Learning Achievement Accounting Through Industrial Work Practices, Work Competence and Self Efficacy as Intervening Variables on the Work Readiness of Class XII Program Students Accounting Skills in Semarang City - Khairani, Desy; Wahyudin, Agus; Pujiati, Amin (Universitas Negeri Semarang, 2019)
Education is a means to improve the quality of human resources. Good education is the expected to be able to create quality human resources and be able to compete in accordance with the demands of the world of work. Vocational high school (SMK) is a place that can create human resources who are ready to work. But in reality, there are many SMK’s alumni have not yet been absorbed into the workforce. The purpose of this study is to examine the effect of accounting learning achievement on student work readiness through industrial work practices, work competence and self efficacy as intervening variables. The population of this research is grade XII students of SMK accounting competence in Semarang City. The total sample of 100 students taken using cluster random sampling technique. Data collection method using a questionnaire. The data analysis method uses descriptive analysis techniques and path analysis with the AMOS program. Results: accounting learning achievement does not affect to work readiness. Industrial work practices do not to affect work readiness. Work competence affects work readiness. Self efficacy does not affect to work readiness. Learning achievement accounting has no effect on the internship. Learning achievement accounting has no effect on work competence. Learning achievement accounting has no effect on self efficacy. Industrial work practices affect self efficacy. Work competence influences self efficacy. Learning achievement accounting through industrial work practices does not affect work readiness. Accounting learning achievement through work competence does not affect work readiness. Accounting learning achievement through self efficacy does not affect work readiness.